2012
DOI: 10.1074/jbc.m112.391508
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Acidic Phospholipids and Nucleotides in Regulating Membrane Binding and Activity of a Calcium-independent Phospholipase A2 Isoform

Abstract: Background: Ca 2ϩ -independent phospholipase A 2 (iPLA 2 ) isoforms mediate the deacylation of phospholipids. Results: Acidic phospholipids and nucleotides associate with the C. elegans iPLA 2 isoform IPLA-1 and modulate its activity. Conclusion: Acidic phospholipids and nucleotides play important roles in regulating iPLA 2 function by enhancing membrane recruitment and promoting enzyme oligomerization. Significance: These findings highlight new regulatory mechanisms that control iPLA 2 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Based on the lipidomic analysis, it is postulated that during embryogenesis, G6PD regulates the activity of PLA 2 s, which are critical for organismal development. 25 , 26 , 27 , 28 , 29 As iPLAs family was considered the main phospholipase in C. elegans , 25 iPLA activity was determined ( Figure 4a ). Compared with mock, iPLA activity was increased in G6PD-deficient adults (2-fold, P <0.05) and even more so in G6PD-deficient embryos (10-fold, P <0.005).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the lipidomic analysis, it is postulated that during embryogenesis, G6PD regulates the activity of PLA 2 s, which are critical for organismal development. 25 , 26 , 27 , 28 , 29 As iPLAs family was considered the main phospholipase in C. elegans , 25 iPLA activity was determined ( Figure 4a ). Compared with mock, iPLA activity was increased in G6PD-deficient adults (2-fold, P <0.05) and even more so in G6PD-deficient embryos (10-fold, P <0.005).…”
Section: Resultsmentioning
confidence: 99%
“…As the major constituents of the biologic membranes, the phospholipids can prevent the stability of cell membrane degeneration and promote recovery via improving cell membrane, protecting cells and mitochondria membrane against injury, promoting synthesis of lipoproteins, and increasing membrane fluidity and enzyme activities (Morrison et al, 2012 ; Zhang et al, 2014 ). Phospholipids also allow selected molecules to diffuse or move across the cell membrane into cells (Bishop and Bell, 1988 ; Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our group found that PEDF and the PEDF-derived peptide 44 mer inhibit oxygen-glucose deprivation-induced oxidative stress through PEDFR/iPLA2 [27]. However, Preeti Subramanian and his colleagues reported that pigment PEDF prevents retinal cell death via PEDF-R and PLA2 enzymatic activity, and it is critical for upregulating Bcl-2 and cell survival [28]. We are not clear which activity played a role to inhibit the activation of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%